Diagnostic and Therapeutic Potential of Extracellular Vesicles. (October 2021) - Kodam, Sai Priyanka; Ullah, Mujib
Extracellular vesicles (EVs) are naturally phospholipid enclosed nanovesicles released by many cells in the body. They are stable in circulation, have low immunogenicity, and act as carriers for functionally active biological molecules. They interact with target organs and bind to the receptors. Their target specificity is important to use EVs as noninvasive diagnostic and prognostic tools. EVs play a vital role in normal physiology and cellular communication. They are known to protect their cargo from degradation, which makes them important drug carriers for targeted drug delivery. Using EVs with markers and tracking their path in systemic circulation can be revolutionary in using them as diagnostic tools. We will discuss the scope of this in this paper. Although there are limitations in EVs isolation and storage, their high biocompatibility will fuel more innovations to overcome these challenges.